2016
DOI: 10.1055/s-0036-1587699
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood Transfusion in the Development of Atrial Fibrillation after Coronary Artery Bypass Grafting

Abstract: Atrial fibrillation (AF) is the most common complication after coronary artery bypass grafting (CABG). It is associated with prolonged hospital stay and increased cost. The aim of this study is to investigate the relationship between transfusion of blood derivatives and occurrence of postoperative paroxysmal AF. From June 2012 to February 2014, 446 patients undergoing CABG with cardiopulmonary bypass (CPB) were prospectively evaluated for occurrence of postoperative AF. Patients and procedural variables were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Most of the previous studies evaluating the association between AF and AKI were designed with a relatively short study period using patients who underwent cardiac surgeries [ 6 , 7 ]. One such study enrolled 446 cardiac surgical patients and found that the development of postoperative AKI was an independent factor associated with new-onset AF [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the previous studies evaluating the association between AF and AKI were designed with a relatively short study period using patients who underwent cardiac surgeries [ 6 , 7 ]. One such study enrolled 446 cardiac surgical patients and found that the development of postoperative AKI was an independent factor associated with new-onset AF [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies evaluating the association between AF and AKI were designed with a relatively short study period using patients who underwent cardiac surgeries [ 6 , 7 ]. One such study enrolled 446 cardiac surgical patients and found that the development of postoperative AKI was an independent factor associated with new-onset AF [ 6 ]. Another prospective study including 2572 cardiac surgical patients disclosed that the occurrence of postoperative AKI carried the 1.7-fold increased risk of developing postoperative AF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies assessed the association of RBC transfusion and the risk of postoperative AF after cardiac surgery. [ 8 , 14 20 ] However, these studies have a modest sample size and convey inconclusive results. To obtain a more comprehensive estimate of the association between BT and the risk of postoperative AF after cardiac surgery, we conducted a meta-analysis to systematically evaluate the association between BT and the risk of postoperative AF in adult patients who had undergone CABG surgery.…”
Section: Introductionmentioning
confidence: 99%